COVID-19 in decompensated cirrhosis - O. V. Tashchyan; M. G. Mnatsakanyan; A. P. Pogromov; I. V. Kuprina; Yu. F. Shumskaya (Вестник трансплантологии и искусственных органов)
Elderly patients with diabetes, hypertension and obesity are at risk of severe course of the novel coronavirus infection COVID-19. Patients with chronic liver disease are also at high risk of severe course and death due to SARS-CoV-2. Case report. Patient D., 65 years old, since 2010, was observed for Child-Pugh class B-C cirrhosis of mixed  etiology (alimentary and metabolic), type 2 diabetes. He was hospitalized on May 17, 2020 due shortness of breath, increased encephalopathy and CT signs of bilateral polysegmental pneumonia, involving about 75% of the lung tissue (CT-scan indicates possible COVID-19-associated pneumonia). Despite repeated negative results of PCR test targeting SARS-CoV-2 viral RNA, the clinical picture and CT scans pointed at the  novel coronavirus infection COVID-19 (virus not identified). Because of decompensated cirrhosis, the patient decided to refrain from antiviral and anticytokine therapy. Oxygen therapy, positional therapy, antithrombotic therapy (fondaparinux sodium), antibacterial therapy (ceftriaxone, then levofloxacin), infusion of 20% albumin solution and fresh frozen plasma were carried out. Due to increasing hypoxemia, the patient was transferred to the ICU and placed under mechanical ventilation. Despite all measures, he developed symptoms of multiple organ failure and died of asystole. Discussion. Mortality in chronic liver diseases, including cirrhosis, under the novel coronavirus infection caused by SARS-CoV-2, reaches 40% [4]. Factors aggravating the novel coronavirus disease in such patients include immune-mediated liver cell damage, direct cytotoxicity resulting from viral replication in hepatocytes, hypoxia, drug-induced liver injury, and reactivation of previously latent liver diseases (including hepatitis B and C virus).Conclusion. In the above clinical case, end-stage lung disease (CT stage 3–4), complicated by disseminated  intravascular coagulation (DIC) syndrome, with progressive respiratory and multiple organ failure, led to the death of the patient suffering from cirrhosis and COVID-19.